Corruption and the Rate of Temptation : Do Low Wages in the Civil Service Cause Corruption? (IMF Working Papers; Working Paper, 1997)
This paper develops and tests two efficiency wage models of corruption in the civil service. Under fair wage models, civil service wages are an important determinant of corruption. Under shirking models, the level of wages is of secondary importance, as potential bribes dwarf wage income. The empirical evidence points to a negative relationship between corruption and wages across developing countries. Tests as to the validity of the two different efficiency wage models are inconclusive.